Factors affecting employee productivity in Block A and B, Perbadanan Putrajaya / Noraliah Shazwani Mohd Taib - Mohd Taib, Noraliah Shazwani (Faculty of Business and Management, 2019)
The paper examines the factors affecting employee productivity in Perbadanan Putrajaya. It examines on employee productivity and the relationship towards working environment, motivation, and compensation. In Malaysian, public sector is one the sector that contribute to the economy in delivering efficient and effective services. Productivity can be evaluated by the amount of output that can be produce in a period of time. It can be seen that employee productivity is important in delivering high quality of services and if the organization did not put into concern towards this matter it will affect the economy. The total population of this study is 288 employees. The questionnaire were conveniently distributed to all the 288 respondents and the total questionnaire that been returned is 225. It represents 78% of response rate. The data collected was processed using Statistical Package for Social Science version 20. The data have been analyzed using reliability analysis, frequency analysis, descriptive analysis, Pearson correlation coefficient analysis and multiple regression analysis. Hence, the results from this study that can be concluded there is a significant and positive relationship between working environment, motivation towards employee productivity. Furthermore, compensation there is no significant and positive relationship towards employee productivity. However from the result, there is other factors that can contribute to employee productivity which is not included in this research. The sample of study is only limited for those who are working in Perbadanan Putrajaya.